The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1073/pnas.0602639103
|View full text |Cite
|
Sign up to set email alerts
|

Fronto-cerebellar systems are associated with infant motor and adult executive functions in healthy adults but not in schizophrenia

Abstract: Delineating longitudinal relationships between early developmental markers, adult cognitive function, and adult brain structure could clarify the pathogenesis of neurodevelopmental disorders such as schizophrenia. We aimed to identify brain structural correlates of infant motor development (IMD) and adult executive function in nonpsychotic adults and to test for abnormal associations between these measures in people with schizophrenia. Representative samples of nonpsychotic adults (n ‫؍‬ 93) and people with sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 35 publications
8
122
0
1
Order By: Relevance
“…In the Northern Finland 1966 birth cohort, those who reached key infant motor milestones earlier had better school performance at 16 years of age and educational attainment at 31 years of age (Taanila et al 2005). Earlier motor development in infancy has been found to be linked with better executive functioning and greater gray matter density and white matter volume in the adult brain (Ridler et al 2006). Another study from the Northern Finland 1966 birth cohort showed that earlier development in the cross motor domain, measured as the age of learning to stand, was associated with better executive functioning at ages 33-35 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Northern Finland 1966 birth cohort, those who reached key infant motor milestones earlier had better school performance at 16 years of age and educational attainment at 31 years of age (Taanila et al 2005). Earlier motor development in infancy has been found to be linked with better executive functioning and greater gray matter density and white matter volume in the adult brain (Ridler et al 2006). Another study from the Northern Finland 1966 birth cohort showed that earlier development in the cross motor domain, measured as the age of learning to stand, was associated with better executive functioning at ages 33-35 years.…”
Section: Discussionmentioning
confidence: 99%
“…In the Northern Finland, 1966 Birth Cohort study earlier infant motor development was found to be associated with better educational outcomes (Taanila et al 2005) and level of intelligence (Murray et al 2007) in adolescence and adulthood. Further, earlier motor development was found to be associated with increased gray and white matter densities and better executive function in adulthood (Ridler et al 2006). However, little is still known about the relationship between early motor development and cognitive functioning in older age.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the existence of neural sharing is that the early infant acquisition of bipedality correlates with enhanced executive skills at the age of 33-35; moreover, half the activated voxels in the cerebellum linked to such adult executive skills also link to those that retrospectively associated with early bipedality (Ridler et al, 2006) (see also further comment in section 7.3). In this context, it should be noted that frontal activations in infants as young as 6 months accompany the maturation of motor skills such as eye saccades depend upon internal models, and, then only later in adults, shift to posterior areas when they become highly automated (Csibra et al, 2001).…”
Section: Developmental Correlation and Neural Overlapmentioning
confidence: 57%
“…If a motor task shares an attentional subprocess with an higher cognitive one (Allen et al, 1997), then it is reasonable to assume that other motor faculties will also share that attentional subprocess. Likewise, if developmentally a motor ability such as bipedality correlates not only in terms of a later competence for executive function but also in 48% of its voxels in the cerebellum (Ridler et al, 2006), it is reasonable to assume that the subprocesses responsible for this is also shared to a similar or greater extent with other motor faculties.…”
Section: Neural Resource Sharing and Nonmotor Facultiesmentioning
confidence: 99%
“…Cerebellar deficits have long been implicated in the origins and evolution of schizophrenia (Andreasen, 1999), and a recent metaanalysis of voxel based morphometry studies of medication naïve psychosis patients identified the cerebellum as one of only two brain regions (the other was the insular cortex) with grey matter volume deficits in antipsychotic naïve patients (Fusar-Poli 2011c). The model developed by Andreasen and colleagues (Andreasen et al, 1998) implicates deficits in the cerebellum producing a so-called "cognitive dysmetria," which entails difficulty in prioritizing, processing, coordinating, and responding to information, and our own previous findings from a related cohort, the Northern Finland 1966 Birth Cohort, provided evidence for abnormal cerebellar neurodevelopment in schizophrenia (Ridler et al, 2006) Of particular interest is our finding that there is a trend in structural cerebellar deficits such that family risk subjects have deficits compared to controls, but not as severe Our study utilises a unique methodology for risk group definition, which presents what we believe is an approach complementary to the majority of brain structural risk for psychosis studies, which tend to be either clinic based or family risk based, as opposed to examining both risk factors within the same population base. The framework we used to study subjects at high risk of psychosis was first to examine the role of single risk factors (clinical or family risk) on brain structure, then analyzing the additive effect of both risk factors (family plus clinical risk).…”
Section: Discussionmentioning
confidence: 99%